Observation and simulation of mountain wave trains in a tropical cyclone situation - Lei, LI; CHAN, P.W.; TSE, S. M. (MAUSAM, 2017)
This paper documents the observations by radar of wave trains downstream of mountains in a tropical cyclone situation. The wind disturbances associated with the wave trains together with the background strong southeasterly flow result in the occurrence of low-level wind shear as detected by the radar. So the case is not just scientifically interesting, but it also has practical application value. The wave trains can be simulated by using a computational fluid dynamics model initialized homogeneously by the upper air ascent data at the time close to that the occurrence of the wave trains. This points to the potential of using such a model in simple setup to forecast the occurrence of low-level wind shear.